Introduction to MathCAD - Larsen, Ronald W. (E Source--the Prentice Hall engineering source, 1999)
For Freshman or Introductory courses in Engineering and Computer Science. ESource-Prentice Hall's Engineering Source-provides a complete, flexible introductory engineering and computing program. Featuring over 15 modules and growing, ESource allows professors to fully customize their textbooks through the ESource website. Professors are not only able to pick and choose modules, but also sections of modules, incorporate their own materials, and re-paginate and re-index the complete project